2001
DOI: 10.1039/b008441g
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of cationic methylallyl, methylindenyl and pentamethylcyclopentadienyl nickel complexes containing the bulky phosphine 1,2-bis(diisopropylphosphino)ethane †

Abstract: A novel high-yield, convenient synthetic method for the complex [Ni(COD) 2 ] has been developed based upon the use of dibutylmagnesium as reducing agent. The cationic complexesether, followed by treatment with dippe and NaBPh 4 in methanol. [Ni(2-MeInd)(dippe)][BPh 4 ] 2 (2-MeInd = 2-methylindenyl) and [Ni(C 5 Me 5 )(dippe)][BPh 4 ] 3 were respectively prepared by reaction of either [Ni(2-MeInd)Br(PPh 3 )] or [Ni(C 5 Me 5 )Br(PPh 3 )] with dippe and NaBPh 4 in methanol. The crystal structures of 1a, 2 and 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The structure of the (dippe)Ni(π-allyl) cation of 6 is similar to that of the closely related analogue [(dippe)Ni(π-2-methylallyl)] + . Also, shorter Ni−C and Ni−P bond distances are observed for 6 than for 3 or 4 , in accord with the increased charge on the metal center (Table ).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The structure of the (dippe)Ni(π-allyl) cation of 6 is similar to that of the closely related analogue [(dippe)Ni(π-2-methylallyl)] + . Also, shorter Ni−C and Ni−P bond distances are observed for 6 than for 3 or 4 , in accord with the increased charge on the metal center (Table ).…”
Section: Resultssupporting
confidence: 55%
“…A 31 P NMR spectrum of the reaction mixture showed, however, that 4 was completely converted to a species displaying a singlet at 83.0 rather than 79.5 ppm. In the 1 H NMR spectrum, a set of sharp resonances that coincide with the resonances of the Ni(II) cation [(dippe)Ni(π-allyl)] + , the precursor used to prepare 3 , were observed instead of the broad resonances associated with 5 . In particular, the appearance of separate, sharp doublet resonances at 4.40 ( J H - H = 7.2 Hz) and 2.43 ( J H - H = 14.4 Hz) ppm for the syn and anti protons of the allyl group clearly indicated that σ−π allyl interconversion does not occur at ambient temperature in this new species ( 6 ), unlike in 5 .…”
Section: Resultsmentioning
confidence: 99%
“…B(C 6 F 5 ) 3 was obtained from Strem. Literature procedures were employed for the preparation of the following compounds: Ni(COD) 2 , Pd(PPh 3 ) 4 , Ni(η 3 -CH 2 C 6 H 5 )Cl(PMe 3 ), NiMe 2 (Py) 2 , trans -NiCl(Ph)(PPh 3 ) 2 , 2-methoxybenzeneboronic acid, 3-bromosalicylaldehyde . All the other chemical products were purchased from commercial vendors and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative synthetic strategy involving displacement of triphenylphosphine from [NiBr 2 (PPh 3 ) 2 ] proved successful for the preparation of 15b, which was isolated in 71% yield following reaction of 3b with the diphosphine complex in MeCN using a modification of a related literature procedure (Scheme 4). 53 Despite repeated attempts using a range of Ni(II) starting materials, reactions involving the tris(aminophosphine)aldimines 4 afford significant quantities of Pr i 2 NH 2 Br as the only identifiable product in each case, irrespective of the solvent employed. Notably, the reaction between equimolar quantities of 3c and [NiBr 2 (DME)] performed in CH 2 Cl 2 under rigorously anaerobic and anhydrous conditions gives rise to the homoleptic bis(pyrrolatoimine) Ni(II) complex trans-[Ni{2-(Mes-N=CH)C 4 H 3 N-j 2 -N,N} 2 ] ( 16) in near-quantitative isolated yield (45%) as a red/brown, air stable solid (Scheme 4).…”
Section: Nickel Dibromide Complexes Of N-pyrrolylphosphino-narylaldim...mentioning
confidence: 99%